The Concept of Independence of Financial Services Authority in Realizing Financial System Stability - Bisdan Sigalingging (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Stability of the Financial System (SSK) as the goal of the Financial Services Authority (OJK) emphasizes a condition that is shock-resistant, easy and accessible to the public, grows sustainably, and is able to protect the interests of consumers and the public. The independence of the OJK in achieving financial system stability is a critical prerequisite for developing an FSS that plays an optimal role in the national economy. However, the concept of independence under Act No. 21 of 2011 still contains inconsistencies and limits independence itself. Subordination of the government (Minister of Finance) with institutions within the OJK structure has the potential to cause problems in the implementation of independence. This normative-juridical research method with secondary data sources and a legal approach concludes Act No. 21 of 2011 still needs to be improved in relation to its independence, subordination, and structure within the Financial System Stability Committee (KSSK), because it has the potential to cause inconsistencies in independence within the Financial System Stability Committee. practice, considering the sector it supervises is very broad and complex. It is hoped that the Minister of Finance's position as chairman of the Pansel should not be permanent so that the independence of the OJK is consistent. The duties, functions, and authorities of each structure within the OJK the Ministry of Finance, Bank Indonesia, and the Deposit Insurance Corporation (LPS) must be determined firmly and measurably and carried out completely independently.